Villes à système productif industriel et gouvernance territoriale - Gérard-François Dumont (Bulletin de l’Association de Géographes Français)
Statistical data indicate a significant decline of industrial employment in France. Deindustrialisation is certainly uneven among territories, especially because two industrial sectors, among the biggest exporters, were job creators in recent years: aerospace and shipbuilding. However, deindustrialisation is often considered fatal, meaning that the industrial cities should all be affected. Yet it appears that local governances result in strong contrasting trends in front of industrial change.